2012
DOI: 10.1530/joe-12-0150
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression differences induced by equimolar low doses of LH or hCG in combination with FSH in cultured mouse antral follicles

Abstract: In a natural cycle, follicle growth is coordinated by FSH and LH. Follicle growth stimulation in Assisted Reproductive Technologies (ART) requires antral follicles to be exposed to both FSH and LH bioactivity, especially after GNRH analog pretreatment. The main aim was to detect possible differences in gene expression in granulosa cells after exposing the follicle during antral growth to LH or hCG, as LH and hCG are different molecules acting on the same receptor. Effects of five gonadotropin treatments were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 72 publications
0
7
0
1
Order By: Relevance
“…In some IVM protocols, assuming that CC can respond to LH, hCG is used as a substitute. However, such a choice does not consider that LH and hCG are not identical, the latter eliciting a different cell response, as shown by recent gene expression studies (Segers et al, 2012).…”
Section: In Vitro Maturation Systemsmentioning
confidence: 99%
“…In some IVM protocols, assuming that CC can respond to LH, hCG is used as a substitute. However, such a choice does not consider that LH and hCG are not identical, the latter eliciting a different cell response, as shown by recent gene expression studies (Segers et al, 2012).…”
Section: In Vitro Maturation Systemsmentioning
confidence: 99%
“…LH is always present in the body, and by stimulating folliculogenesis in vivo it is possible to obtain concentrations that are sufficient for follicle maturation (Gal et al ., 2014). LH has not always been considered a necessary component of the culture medium, but currently the question of its positive influence on follicular growth in vitro is being actively discussed (Segers et al ., 2012; Park et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, eCG treatment induced Cyp19a1 , which is known to increase in response to FSH and is a rate‐limiting enzyme for estrogen synthesis in granulosa cells of multiple species (Hillier, 1994; Parakh et al, 2006; Stocco, 2008; Verbraak et al, 2011). We also found that eCG‐induced Cyp11a1 , which catalyzes the conversion of cholesterol to pregnenolone (Segers, Adriaenssens, Wathlet, & Smitz, 2012; Wigglesworth, Eppig, Lee, Emori, & Sugiura, 2015). It was shown, using microarray analysis, in cultured bovine granulosa cells that FSH induced both CYP19A1 and CYP11A1 at 4 h after treatment (Nivet et al, 2018).…”
Section: Discussionmentioning
confidence: 90%
“…We also found an increase in Lanosterol synthase ( Lss ) at 48 h eCG (2.5‐fold). Lss functions as a catalyst in cholesterol biosynthesis and is induced by FSH (Fan et al, 2009; Segers et al, 2012). The promoter of Lss , like Fshr also had H3K4me3 enrichment although this was not significantly regulated by FSH.…”
Section: Discussionmentioning
confidence: 99%